High prevalence of extensively drug-resistant and metallo beta-lactamase-producing clinical Acinetobacter baumannii in Iran. (September 2016) - Maspi, Hossein; Mahmoodzadeh Hosseini, Hamideh; Amin, Mohsen; Imani Fooladi, Abbas Ali
Abstract: Acinetobacter species particularly Acinetobacter baumannii (A . baumannii ) have been widely reported as broad-spectrum antibiotic resistant pathogens. Expression of various types of metallo beta-lactamases (MBL), classified as Ambler class B, has been associated with carbapenem resistance. Here, we attempted to assess the frequency of extensively drug-resistant (XDR) and MBL-producing A . baumannii among clinical isolates. 86 clinical A . baumannii strains were collected from 2014 to 2015 and their susceptibility to meropenem (10 μg), imipenem (10 μg), azteronem (30 μg), pipracillin (100 μg) tazobactam (110 μg), tobramycin (10 μg), fosfomycin (200 μg), rifampicin (5 μg), colistin (10 μg), tigecycline (15 μg), sulbactam/ampicillin (10 μg + 10 μg) and polymixin B (300 U) was evaluated using disk diffusion method. The MBL-producing isolates were screened using combined disc diffusion method. Furthermore, the presence of bla VIM, bla IMP, bla SPM, bla GIM, bla SIM and bla NDM was detected by PCR. 34.9% of isolates were recovered from bronchoalveolar lavage (BAL). 81 (94.2%) and 62 (71.2%) isolates were multidrug resistance (MDR) and XDR, respectively. 44 (51.2%) and 65 (75.6%) isolates were MBL-producing strains with resistance to imipenem and meropenem, respectively. 2 (2.3%), 13 (15.1%), 2 (2.3%), 4 (4.7%) and 2 (2.3%) isolates carried bla VIM, bla IMP, bla SPM, bla GIM and bla SIM genes, respectively. Our data showed that the rate of XDR and MBL A . baumannii is on the rise. Highlights: Our data showed higher resistance rate to carbapenem even compared to previous reports. The vast majority of our isolates were XDR with high resistance to colistin. High resistance to colistin and polymixin is alarming due to limited antibiotic prescription for A. baumannii infections. This is the first report about the prevalence of A. baumannii carrying blaSPM, blaGIM and blaSIM genes from Iran.